Investigation of radionuclide ¹³⁷Cs sorption by natural and synthetic zeolites - Lonin, A.Yu.; Krasnopyorova, A.P. (Вопросы атомной науки и техники, 2004)
Sorption-selective properties of natural zeolite-clinoptilolite, from the Sokirnitsky deposit of Ukraine, and synthetic zeolites relatively to radionuclide ¹³⁷Cs and depending on pH and temperature were studied. A high sorption ability of clinoptilolite relatively to ¹³⁷Cs was determined. Вивчено сорбційно-селективні властивості природного цеоліту кліноптілоліта Сокирницького родовища України і синтетичних цеолітів щодо радіонукліда ¹³⁷Cs у залежності від рН і температури. Установлено високу сорбційну здатність кліноптілоліту у відношенні до ¹³⁷Cs. Изучены сорбционно-селективные свойства природного цеолита клиноптилолита Сокирницкого месторождения Украины и синтетических цеолитов относительно радионуклида ¹³⁷Cs в зависимости от рН и температуры. Установлена высокая сорбционная способность клиноптилолита в отношении ¹³⁷Cs.